Kajian Konsep Pengembangan Pariwisata Berbasis Masyarakat Melalui Kearifan Lokal di Desa Wisata Terong Kabupaten Belitung - Aliyatun Nurul Hasanah; M. Sapari Dwi Hadian; Alexander M.A. Khan (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2021)
Through Laskar Pelangi movie, Belitung becomes the spotlight of tourists to be a tourist destination. Many people develop their villages to become tourist destinations, such as Terong Village. Terong Village started the development of tourist areas in 2016 and has four tourist destinations, namely Aik Rusa'Berehun Destination, Bukit Tebalu Simpar Laki Tourism Destination, Agrotourism Destination of Terong Belitung Village, and Mangrove and Beach Tourism Destinations. Besides tourism object, there are important things to do to attract tourists to come to Terong Village, namely about Local Wisdom from Eggplant Village itself, such as language, traditional dance, traditional food, and so on. Local wisdom is able to attract more tourists to visit The Eggplant Village if appropriate development is carried out. Through this study, the author has an idea to conduct research on the development of Terong Village tourism through Local Wisdom based on the development of the village community. Research is carried out by literacy study method, which is looking for similar studies and analysis of the source of the study.